The Process of Development of the Personality in the Novel by Leonov "Skutarevsky" - Kuzmenko, S. (Literatūra, 1975)
The „change-over“ of Skutarevsky is represented by Leonov as a component part of the whole process of soiritual renovation of t-he personality under the epoch of socialism. This process reflects the essential features of the Soviet life of the twenties - thirties of the twentieth century: i. e. the development of man as a maker of history resulting in stirring up the great mass enthusiasm concealed in the consciousness of the masses (the character of Matvey Cherimov), the revival of human creative activity suppressed under the condition of exploitation system hostile to the real culture and real art (the character of Fyodor Skutarevsky) and so·forth. The characters of the novel symbolize the great animating force of new social relations. The „smoothing“ of not only separate sides of the personality, being stimulated to reaoh its apprapriate level in all spheres of public life (Skutarevsky, Cherimov) but of various types of social groups (the proletariat, the scientific and creative intelligentsia, the peasantry et al), the gradual obliteration of the- whole series of essential distinctions among classes and groups of the working people and acquisition by them of more and more important general features in the construction of new life are going on under the conditions of new social system. The above-mentioned development is depicted in the novel as the beginning of the great process of foundation of the single type of personality which will reach its peak in the developed communist society.